The Influence Of Servant Leadership And Intrinsic Motivation On The Performance Of Employees Of The Inamosol Sub-District Office, Western Seram District - Mohammad Amin (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The purpose of this study was to determine and analyze the effect of servant leadership, intrinsic motivation, and employee performance at the Inamosol Sub-District Office, West Seram Regency. The research approach that will be used in this research is a quantitative approach. In this study, the population in this study were all employees of the Inamosol Sub-District Head of West Seram Regency totaling 34 people, where the entire population was used as a research sample using the saturated sample method, the sample used was 34 people. The data were analyzed using the classical assumption test, multiple linear regression, hypothesis testing and the coefficient of determination test. Data processing using SPSS software The results showed that servant leadership, intrinsic motivation had a significant and positive effect on employee performance at the Inamosol Sub-District Office, West Seram Regency.